Apoptosis as a mediator of hyperplastic recovery in human prostate lesions: cytochemical and immunocytochemical evaluation - Taboga, SR (Faculty Press, 1999)
The present study was carried out to investigate the occurrence of apoptosis in human prostatic lesions with emphasis on nodular hyperplasia and adenocarcinomas, using cytochemistry and immunocytochemistry. The results showed that apoptosis is a common event on nodular hyperplasia but not in adenocarcinomas. This led to the hypothesis that apoptosis may represent an important factor on the localized recovery response of the hyperplastic acini.
Keywords: apoptosis; prostate; prostatic nodular hyperplasia; Cytochemistry; critical electrolyte concentration